2019
DOI: 10.1016/j.heliyon.2019.e02503
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for bridging the theory-practice gap from the perspective of nursing experts

Abstract: The gap between education and the clinical practice has always been challenge for educational experts in the field. This article aims to explore the perspective of Iranian nursing experts about strategies used for coordinating education and clinical performance in nursing. This qualitative study was conducted by using a conventional content analysis approach; individual interviews were conducted at the participants’ work place; while focus group discussions took place at the Nursing and Midwifery Faculty of Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 25 publications
1
31
0
1
Order By: Relevance
“…In another qualitative study conducted among undergraduate students in Jordan, students voiced that they did not receive good support in the clinical area, with some explaining that their instructors were sometimes busy in other managerial issues, decreasing the time left teaching for students [ 16 ]. The disparity in ratio between instructor and students was also highlighted in a study by Shoghi, Sajadi [ 21 ], where it was revealed that nurse-to-nurse faculty/clinician ratio increased with large admissions, and consequently reduced the value and extent of learning experiences in the clinical environment.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In another qualitative study conducted among undergraduate students in Jordan, students voiced that they did not receive good support in the clinical area, with some explaining that their instructors were sometimes busy in other managerial issues, decreasing the time left teaching for students [ 16 ]. The disparity in ratio between instructor and students was also highlighted in a study by Shoghi, Sajadi [ 21 ], where it was revealed that nurse-to-nurse faculty/clinician ratio increased with large admissions, and consequently reduced the value and extent of learning experiences in the clinical environment.…”
Section: Discussionmentioning
confidence: 96%
“…Several international studies from UK, Ireland, Turkey and the US have identified the importance of collaboration between nursing instructors, nurses, nursing school and hospital managements as one of the most suggested means of bridging the gap [ 14 , 15 , 20 , 21 ]. Several studies showed the importance of the availability of adequate number of well-trained academics and clinical preceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Nursing education seeks to provide the necessary theoretical background and technical competencies to meet healthcare system demands and produce workforce‐ready graduates. The dichotomy between the theoretical knowledge taught in the classroom and the competencies performed in the wards remains an entrenched problem for nursing educators and practitioners; this gap is most apparent among newly graduated, novice nurses (Greenway et al, 2019; Huston et al, 2018; Monaghan, 2015; Shoghi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As Shoghi et al. (2019) found, the establishment of a joint committee between the two groups is an effective way to bridge the gap between the two arenas and develop the academic–practice relationship. A committee would jointly establish realistic expectations, what is needed in the transition, and identify the desired future state of the NGNs' transition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has supported the persistence of a theory–practice gap (Akram et al., 2018; Safazadeh et al., 2018; Shoghi et al., 2019; Weeks et al., 2019), and bridging the gap has largely fallen on the shoulders of nursing education. While some studies have included the voices of students (Akram et al., 2018; Roldán‐Merino et al., 2019), nurse educators (van Zyl, 2014), practising nurses (Bennett et al., 2017) or all three together (Safazadeh et al., 2018; Salifu et al., 2018), very few included the perspectives of health care administrators (Shoghi et al., 2019). Health care administrators can help bridge the theory–practice gap because they understand NGNs' strengths and gaps in knowledge, the needs of their practice areas and organisations, and the trends and issues within health care.…”
Section: Introductionmentioning
confidence: 95%